Understanding the demographic and socioeconomic determinants of morbidity in Eastern Uganda: a retrospective analysis of the Iganga-Mayuge health and demographic surveillance data - Dan Kajungu; Henry Owoko Odero; Agnes Kiragga; Steve Bicko Cygu; Betty Nabukeera; Lindsey English; Shakira Babirye; Collins Gyezaho; Maureen Ng'etich; Michael Ochola; David Amadi; Grace Banturaki; et al. (BMJ Public Health)
Introduction Understanding the determinants of disease burden is imperative in enhancing population health outcomes. This study uses data from the Iganga-Mayuge Health and Demographic Surveillance Site, to understand demographic and socioeconomic factors influencing morbidity.Methods We analysed secondary data from 2018 to 2023. We employed graphs and tables to present morbidity patterns across different sociodemographic factors and applied mixed-effects multinomial multivariate logistic regression model to understand the correlates of morbidity.Results The findings reveal a predominant prevalence of malaria, lower respiratory tract infections, coryza, gastric acid-related and urinary tract infections, collectively constituting 83% of diagnosed diseases. Noteworthy demographic variations, particularly gender and age, significantly impact disease distribution, revealing higher diagnosis rates among females. Additionally, socioeconomic factors, including education and wealth status, contribute to discernible differences in disease burden.Conclusion This research provides crucial insights into the implications of demographic and socioeconomic factors on disease burden in Uganda. The results contribute to evidence-based policy-making, highlighting the necessity for targeted interventions addressing specific health challenges encountered by diverse populations. The study advocates for continuous assessment of the epidemiological landscape to inform more tailored and effective health strategies, ultimately enhancing resilience in disease control efforts.